PENERAPAN MODEL DISCOVERY LEARNING DENGAN MEDIA KARTU DOMINO DALAM PENINGKATAN PEMBELAJARAN PENJUMLAHAN PECAHAN - Sa'diyah, Awalus; Triyono, Triyono; Susiani, Tri Saptuti (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Use Of Discovery Learning Model Using Domino Card Media in Improving The Learning Of The Addition Of Fraction For Fourth Grade Students Of SD Negeri Ampelsari in The Academic Year Of 2016/2017. The objective of this research is to improve the learning of the addition of fraction through the use of discovery learning model using domino card media. Subjects of the research were 30 students of fourth grade. This research is a collaborative Classroom Action Research (CAR). Techniques of collecting data were test and non-test (observation and interview). The validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Data were analyzed using descriptive qualitative analysis and statistic descriptive analysis. The results of this research show the use of Discovery learning model using domino card media can improve the learning of the addition of fraction for fourth-grade students. Keywords: Discovery Learning, Domino Cards Media, Learning, Fraction Abstrak: Penerapan Model Discovery Learning dengan Media Kartu Domino dalam Peningkatan Pembelajaran Penjumlahan Pecahan pada Siswa Kelas IV SD Negeri Ampelsari Tahun Ajaran 2016/2017. Tujuan penelitian ini yaitu meningkatkan pembelajaran penjumlahan pecahan melalui penerapan model Discovery Learning dengan media kartu domino. Subjek penelitian ini adalah siswa kelas IV. Penelitian ini adalah penelitian tindakan kelas kolaboratif. Teknik pengumpulan data adalah teknik tes dan non-tes yang terdiri dari observasi dan wawancara. Validitas data menggunakan triangulasi sumber data dan triangulasi teknik. Analisis data menggunakan analisis deskriptif kualitatif dan analisis statistik deskriptif. Hasil penelitian penerapan model discovery learning dengan media kartu domino dapat meningkatkan pembelajaran penjumlahan pecahan. Kata Kunci: discovery learning, media kartu domino, pembelajaran, pecahan.